2003
DOI: 10.1210/en.2002-220811
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-α Activation during Pregnancy Attenuates Glucose-Stimulated Insulin Hypersecretion in Vivo by Increasing Insulin Sensitivity, without Impairing Pregnancy-Induced Increases in β-Cell Glucose Sensing and Responsiveness

Abstract: We investigated the effects of acute (24-h) peroxisome proliferator-activated receptor (PPAR)alpha activation by WY14,643 (pirinixic acid) treatment on glucose-stimulated insulin secretion (GSIS) during pregnancy, in the rat, in relation to insulin sensitivity. GSIS after iv glucose challenge (500 mg/kg) was increased at d 15 of pregnancy but was attenuated by WY14,643 treatment in vivo, with decreases in acute insulin response (51%; P < 0.001) and total suprabasal 30-min area under the insulin curve (deltaI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 42 publications
2
33
1
Order By: Relevance
“…Samples of the media outflow are collected throughout the experiment, every one to two minutes, and the insulin content is then determined to obtain a rate of insulin release. The number of islets used in perifusion experiments varies from 5 to as many as 50 [5][6][7][8][9]. In perifusion experiments, the concentration vs. time profile of secreted insulin can be compared to the expected glucose stimulated insulin response for healthy islets [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Samples of the media outflow are collected throughout the experiment, every one to two minutes, and the insulin content is then determined to obtain a rate of insulin release. The number of islets used in perifusion experiments varies from 5 to as many as 50 [5][6][7][8][9]. In perifusion experiments, the concentration vs. time profile of secreted insulin can be compared to the expected glucose stimulated insulin response for healthy islets [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This is normally accompanied by a lowered glucose threshold for insulin secretion and increased insulin secretion at high glucose concentration [5,36,37], which compensates for the development of insulin resistance so that glucose tolerance is maintained. We found that hyperthyroidism during late gestation targeted both of these stable pancreatic beta cell adaptations to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated islets were collected into HEPESbuffered Hanks' balanced salts solution containing 5% BSA. Insulin release was measured in a perifusion system, as described previously [5,33]. In this system, 50 islets were housed in small chambers on Millicell culture plate inserts (Sigma, Poole, Dorset, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations